Cultivos de cobertura: dinámica de la descomposición de residuos sobre y dentro del suelo - Rampo, Mauro Javier; Giron, Paula; Barraco, Miriam Raquel; Miranda, Walter; Lobos, Horacio Martín; Frasier, Ileana (Asociación Argentina Ciencias del Suelo, 2021)
Ponencia